HUBUNGAN PERSEPSI DAN DAYA TERIMA MAKANAN ANAK ASRAMA DENGAN KEJADIAN ANEMIA PADA SISWI SMP SWASTA GALIH AGUNG PESANTREN DARUL ARAFAH RAYA - Br Sitepu, Nur Syah Ainun; Angkat, Abdul Hairuddin (Smart Education, 2025)
Abstract: Anemia is one of the health problems throughout the world, especially in developing countries. Anemia often occurs in adolescence because during that period adolescents experience reproductive organ maturation. One of the causes of anemia is food intake which includes the problem of not paying attention to eating according to the nutritional needs of adolescents, often consuming fast food and often ignoring meal times.The purpose of the study was to determine the correlation between perception and food acceptance of boarding school children with anemia incidence in Private Junior High School Students of Galih Agung Islamic Boarding School Darul Arafah Raya.This study was an Observational study with a Cross-Sectional research design. A total of 71 female students were taken as samples. Data collection using questionnaire instruments and hemoglobin level checkers. Data analysis using the Chi-Square Test.The results showed that the incidence of anemia in female students was 56.3%. There was no correlation between female students' food perceptions and the incidence of anemia, obtained a statistical test result value of p = 0.542 (p> 0.05). There was a correlationbetween food acceptance and anemia, obtaining a statistical test result value of p = 0.011 (p <0.05). Conclusion There was no correlationbetween female students' food perceptions and the incidence of anemia and There was a correlationbetween food acceptance and anemia. Keyword: Guardianship, Revocation and Transfer of Guardian, Inheritance Anemia, Adolescents, Food Perception, Food Acceptance Abstrak: Anemia merupakan salah satu masalah kesehatan diseluruh dunia terutama negara berkembang. Anemia sering terjadi pada usia remaja dikarenakan pada periode tersebut remaja mengalami pematangan organ reproduksi. Salah satu penyebab terjadinya anemia adalah asupan makanan yang meliputi masalah kurangnya memperhatikan makan sesuai dengan kebutuhan gizi remaja, seringnya mengkonsumsi makanan siap saji dan sering mengabaikan waktu makan. Tujuan penelitian untuk mengetahui hubungan persepsi dan daya terima makanan anak asrama dengan kejadian anemia pada Siswi SMP Swasta Galih Agung Pesantren Darul Arafah Raya.Penelitian ini merupakan penelitian Observasional dengan rancangan penelitian Cross Sectional. Sampel diambil secara keseluruhan sebanyak 71 siswi. Pengumpulan data menggunakan instrumen kuesioner dan alat pemeriksa kadar hemoglobin. Analisis data menggunakan Uji Chi-Square.Hasil penelitian menunjukkan bahwa angka kejadian anemia pada Siswi sebanyak 56,3%. Tidak ada hubungan antara persepsi makanan siswi dengan kejadian anemia diperoleh nilai hasil uji statistik yaitu p = 0,542 (p > 0,05). Terdapat hubungan antara daya terima makanan dengan anemiadiperoleh nilai hasil uji statistik yaitu p = 0,011 (p < 0,05). Kesimpulan tidak ada hubungan antara persepsi makanan siswi dengan kejadian anemia dan Terdapat hubungan antara daya terima makanan dengan anemia. Kata kunci: Anemia, Remaja, Persepsi Makanan, Daya Terima Makanan